Cationized Lignocelluloses as Scavengers for Anionic Surfactants. II. Hydrophobic Interactions - Haïfa Zghida; Robert Gauthier; Ahmed Helal (Adsorption Science & Technology)
As reported in Part I of this study, anionic surfactants are rapidly adsorbed and strongly retained on cationized lignocellulosic materials as a result of ionic interactions. Consequently, the initially hydrophilic surface of the sorbent is strongly modified by the adsorbed surfactant molecules. Hydrophobic interactions with this modified surface allow a second layer of surfactant molecules to be adsorbed via their alkyl chains. Many combinations are possible with different kinds of surfactants, with the highest adsorption capacity being obtained when zwitterionic surfactants are involved in the second step.